2019
DOI: 10.1021/acs.langmuir.9b01153
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Redox-Triggered Morphology Transitions of Supramolecular Self-assemblies with pH Responsiveness for Triple-Controlled Release

Abstract: The realization of multistage-controlled drug delivery at the cell level through the morphology transitions of supramolecular self-assemblies (SSA) is still a challenge. Herein, successive morphology transitions of SSA with pH responsiveness were successfully achieved through the subsequent action of ultrasound and redox stimuli. Specifically, we first prepared noncovalently PEGylated spherical self-assemblies formed by host−guestconjugated amphiphilic β-CD dimers. The functionalized PEG could be associated/di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Hai Yao and co-workers reported a triple-stimuli responsive supramolecular self-assembly for the sustained release of DOX [31]. The initial spherical selfassemblies (ISSA) were formed from E-CD dimers (Fc-https://doi.org/10.1051/e3sconf/202130 E3S Web of Conferences 309, 01014 (2021) ICMED 2021 901014 CD2) which was generated by linking E -CD which with ferrocene (Figure 3a).…”
Section: Multiple Stimuli Responsive CD Based Materialsmentioning
confidence: 99%
“…Hai Yao and co-workers reported a triple-stimuli responsive supramolecular self-assembly for the sustained release of DOX [31]. The initial spherical selfassemblies (ISSA) were formed from E-CD dimers (Fc-https://doi.org/10.1051/e3sconf/202130 E3S Web of Conferences 309, 01014 (2021) ICMED 2021 901014 CD2) which was generated by linking E -CD which with ferrocene (Figure 3a).…”
Section: Multiple Stimuli Responsive CD Based Materialsmentioning
confidence: 99%
“…The rod–coil molecule composed of flexible and rigid blocks, is a unique compound that combines self-assembly ability and functional characteristics for the construction of soft materials. , The anisotropic orientation of the rigid part and the repulsive effect between the rod and coil segments lead to the self-assembly and formation of various aggregate structures. , Jin et al have reported on the self-assembly of many rod–coil diblock and coil–rod–coil triblock compounds. The effect of rigidity and flexibility ratios on supramolecular assembly was studied, and investigated the effect of external stimuli on self-assembled nanostructure. The main difference between the rod–coil–rod compound and the rod–coil or coil–rod–coil compound system is that the rigid components of the rod–coil–rod compound have rigid components at both ends, and the interaction between the rigid parts of molecules is able to form a more stable folding conformation in solution. Although the research on rod–coil systems is very exciting, there have been few studies on the self-assembly of rod–coil–rod composites with DSA core to improve photoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the transport efficiency of free drugs into nucleus is relatively low, resulting in unsatisfactory therapeutic effects . Therefore, numerous delivery systems have been explored to enhance delivery efficacy via improving tumor tissue accumulation or increasing cellular uptake of the free drug . However, in many delivery systems, the payloads are typically delivered to the cytoplasm or even entrapped in the endosome/lysosome, resulting in failure to reach the final destination of the nuclei .…”
Section: Introductionmentioning
confidence: 99%